Czynniki związane z występowaniem depresji u osób dorosłych. Przegląd systematyczny literatury polskiej w latach 2009-2014 = Factors related to occurrence of depressive disorders in adults. A systematic review of Polish literature in years 2009-2014 - Karolina Jasik; Urszula Jaślikowska; Marta Zbrojkiewicz; Barbara Ślusarska; Magdalena Jasińska; Magdalena Grzegorczyk; Grzegorz Józef Nowicki (Kazimierz Wielki University, 2016)
Jasik Karolina, Jaślikowska Urszula, Zbrojkiewicz Marta, Ślusarska Barbara, Jasińska Magdalena, Grzegorczyk Magdalena, Nowicki Grzegorz Józef. Czynniki związane z występowaniem depresji u osób dorosłych. Przegląd systematyczny literatury polskiej w latach 2009-2014 = Factors related to occurrence of depressive disorders in adults. A systematic review of Polish literature in years 2009-2014. Journal of Education, Health and Sport. 2016;6(4):297-318. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50206 http://ojs.ukw.edu.pl/index.php/johs/article/view/3472   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016.   Czynniki związane z występowaniem depresji u osób dorosłych. Przegląd systematyczny literatury polskiej w latach 2009-2014 Factors related to occurrence of depressive disorders in adults. A systematic review of Polish literature in years 2009 - 2014   Jasik Karolina1, Jaślikowska Urszula1, Zbrojkiewicz Marta1, Ślusarska Barbara2, Jasińska Magdalena1, Grzegorczyk Magdalena1, Nowicki Grzegorz Józef2   1Studenckie Koło Naukowe Katedry Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu Uniwersytet Medyczny w Lublinie 2Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie   Słowa kluczowe: depresja, czynniki etiologiczne, przegląd systematyczny, literatura polska, lata 2009-2014 Key words: depression, etiological conditions, systematic review, Polish literature, years 2009-2014   Streszczenie Wstęp: Stały wzrost liczby chorych na depresję w społeczeństwach krajów rozwiniętych jest sygnałem dla wnikliwej analizy polietiologicznych ich uwarunkowań. W społeczeństwie dorosłych Polaków zaburzenia depresyjne zalicza się także do częstych problemów zdrowotnych. Cel: Określenie czynników związanych z występowaniem depresji u osób dorosłych w przeglądzie literatury polskiej w latach 2009-2014. Materiał i metoda:Dokonano przeglądu systematycznego literatury polskiej latach 2009-2014. Przeszukano elektroniczne bazy danych oraz opublikowane wyniki badań. Aby zidentyfikować doniesienia spełniające wybrane kryteria selekcji, zastosowano wieloetapowy proces wyboru, a następnie poddawano prace krytycznej ocenie. Wyniki: W analizowanym okresie znaleziono 1067 artykułów zawierających użyte hasła. Do pełnej wersji zakwalifikowano 31 prac, które spełniały wszystkie kryteria włączenia. Wśród zakwalifikowanych prac najczęściej stosowanymi narzędziami oceny depresji były: Skala depresji Becka (BDI) - w 21 badaniach, Skala depresji i lęku (HADS) - w 4 badaniach oraz Skalę geriatrycznej oceny depresji (GDS) - w 4 badaniach. Przeanalizowano dane 3607 osób, w tym 1789 osób z rozpoznaną depresją. Wnioski: Głównymi przyczynami depresji w grupie osób objętych analizą było: pełnienie roli opiekuna nad przewlekle chorym członkiem rodziny (69,7%) oraz występowanie wśród ankietowanych choroby przewlekłej (65,3%).   Abstract Introduction. Constant increase in number of people suffering from depression in societies of developed countries is a signal for thorough analysis of their polyethologic conditions. In society od Polish adults, depression is also classified as frequent health problems. Purpose.Determining the factors related to occurrence of depression in adults in Polish society in years 2009 - 2014. Material and method. A systematic review of Polish literature in years 2009-2014 was undertaken. The electronic databases and published study results were searched through. In order to identify reports meeting selection criteria, the multi-stage selection process was used, and then the projects were critically evaluated. Results. There were 1067 articles including used keywords found in the analysed period. 31 articles were qualified for the research analysis as they fulfilled all of the inclusion criteria. Among the qualified projects, the most frequently used tools of depression evaluation were: Beck Depression Inventory (BDI) - in 23 projects, Hospital Anxiety and Depression Scale (HADS) - in 4 projects, and Geriatric Depression Scale (GDS) - in 4 projects. In total, data from 3607 persons with recognized depression were analysed. Conclusions. The main causes for depression in the analysed group were: acting as caregiver of chronically ill family member (69,7%) and occurrence of chronic disease among respondents (65,3%).